Motivasi Orang tua Memilih Pondok Pesantren sebagai Sarana Pembinaan Akhlak - Adila, Citra; Darmaningrum, Khaerunnisa Tri (IAINU Kebumen, 2023)
In general, parents are motivated to choose Islamic boarding schools as a place to seek knowledge. Considering the rapid pace of technology, parents are worried about their children, they want theirchildren to get a better education. Parents are afraid that their children will be influenced or involved in promiscuity, so they ultimately choose Islamic boarding schools as a means of developing their children's morals. They believe that Islamic boarding school institutions are capable of educating and developing children's morals. This research focuses on two studies, namely, first, what motivates parents to choose Islamic boarding schools as a means of developing children's morals in Kranggan Village,Tersono District, Batang Regency? Second, what are the opportunity and inhibiting factors in the process of moral development in Islamic boarding schools? This research uses descriptive research methods with a qualitative approach. The data sources for this research are parents/guardians of santri, santriwan/i and local village community leaders. Data collection in research is by interviews, observation and documentation. The results of this research are the motivation of parents to choose Islamic boardingschools as a place for moral development, parents want their children to gain useful knowledge and have noble morals. However, there are opportunity and inhibiting factors in the moral development process